Advances in the study of key cells and signaling pathways in renal fibrosis and the interventional role of Chinese medicines - Liang, Lijuan; Mi, Youjun; Zhou, Shihan; Yang, Aojian; Wei, Chaoyu; Dai, Enlai (Frontiers in Pharmacology, 2024)
Renal fibrosis (RF) is a pathological process characterized by the excessive accumulation of extracellular matrix (ECM), which triggers a repair cascade in response to stimuli and pathogenic factors, leading to the activation of molecular signaling pathways involved in fibrosis. This article discusses the key cells, molecules, and signaling pathways implicated in the pathogenesis of RF, with a particular focus on tubular epithelial cells(TECs), cellular senescence, ferroptosis, autophagy, epithelialmesenchymal transition (EMT), and transforming growth factor-β (TGF-β )/Smad signaling. These factors are critical in driving the core and regulatory pathways that significantly influence RF. A comprehensive understanding of their roles is essential.Additionally, through a literature review, we explore recent advancements in Traditional Chinese Medicine (TCM) aimed at reducing RF and inhibiting chronic kidney disease (CKD). We summarize, analyze, and elaborate on the important role of Chinese herbs in RF, aiming to provide new directions for their application in prevention and treatment, as well as scientific guidance for clinical practices.